Overcoming denominator problems in refugee settings with fragmented electronic records for health and immigration data: a prediction-based approach - Erdmann, Stella; Jahn, Rosa; Rohleder, Sven; Bozorgmehr, Kayvan (BMC medical research methodology, 2024)
Epidemiological studies in refugee settings are often challenged by the denominator problem, i.e. lack of population at risk data. We develop an empirical approach to address this problem by assessing relationships between occupancy data in refugee centres, number of refugee patients in walk-in clinics, and diseases of the digestive system.
Gesehen am 14.06.2024